EVALUASI PEMBENTUKAN PEKERJA SOSIAL MASYARAKAT BERDASARKAN PERATURAN MENTERI SOSIAL NOMOR 10 TAHUN 2019 TENTANG PEKERJA SOSIAL MASYARAKAT DI KABUPATEN MADIUN PROVINSI JAWA TIMUR - Herning Suryo Sardjono; Sundari Sundari; Suwardi Suwardi (Master of Public Administration, Universitas Slamet Riyadi, 2023)
Community Social Workers are potential sources of social welfare and ascommunity members who have a spirit of social service, willingness, the abilityalso have an important role in the implementation of social welfare.This study describes the formation of community social workers in MadiunRegency using a qualitative approach and descriptive research methods.The evaluation of the formation of community social workers based on theMinister of Social Affairs Regulation Number 10 of 2019 uses three indicators,namely input, convention process, and output.Input: Regulations, Human Resources, Facilities and Infrastructure, and Budgetavailable at the Social Service Office of Madiun Regency.Conversion process: implementation stages starting from recruitment,verification, and validation, determination of candidates, basic technicalguidance, determination of community social workers decision letters.Output: Decision of the Head of the Social Service Office of Madiun RegencyNumber: 188.45/171/KPTS/402.111.2021 concerning Community Social Workersof Madiun Regency in 2021 in the appendix totaling 41 people, 31 villages, 15sub-districts which were set on October 1, 2021, also formed the Workers'Association Social Society.Keywords: Evaluation, Community Social Worker, Madiun District Social Service